AIR-COUPLED ULTRASONIC EVALUATION TECHNOLOGY FOR VISCOELASTIC PROPERTY OF MATERIALS - LIN DanYi; ZHU LiJun; ZHANG YiHua (Jixie qiangdu, 2018)
In view of the deficiencies of the main evaluation methods of viscoelasticity,the air-coupled ultrasonic evaluation technology was introduced with the characteristics of non-contact and nondestructive. Based on the theory of viscoelasticity and air-coupled ultrasonic,the theory and experimental method of the air-coupled ultrasonic evaluation for viscoelsaticity were proposed. The storage modulus,loss modulus and loss angle tangent were achieved through the measurement of reflection coefficient,wave velocity and attenuation coefficient. The testing study of air-coupled ultrasonic evaluation for viscoelasticity was carried out,the method was compared with the DMA testing,the results were very consistent. The advancement and accuracy of air-coupled ultrasonic evaluation for viscoelsaticity was proved.